Consumer perceptions of private label brands: an Eastern Cape university-aged analysis - Mpofu, Bukhosi Dumoluhle (Rhodes University, Faculty of Commerce, Department of Management, 2011)
This research investigates the consumer perceptions of private label brands amongst the university aged consumers from selected Eastern Cape universities. The research also aimed to ascertain whether or not generation Y consumers are aware of the existence of private labels, whether price, quality, advertising, packaging, reference groups and demographic variables influenced generation Y purchasing behavior of private label brands. To achieve these objectives, the research made use of the simple random technique to gather the primary data via the use of an online structured questionnaire. The sample population selected where the students in the Eastern Cape Province Universities (Rhodes and Nelson Mandela Metropolitan Universities) who reside off-campus. The assumption was that students who reside off-campus are more aware of private labels as they carry out shopping more than those that reside on campus and generally would have more disposable income and the reason that two different universities have been chosen is to provide a broad base of student opinions, covering varying cultural and income backgrounds, thus allowing for unbiased, valuable research. After pre-tests were conducted the questionnaire was made available online to easy the distribution of the questionnaire and allow for a greater response rate. Descriptive and inferential statistics where used to analyze the results of the questionnaire. The results showed that consumers are generally aware of private label brands and have at least seen them being advertised. Furthermore, the results showed that consumers purchase groceries based on price, quality and convenience of location of the grocery stores .The results indicate that Generation Y consumers are indeed a significant part of the consumer population and that they represent a confident, self reliant, optimistic and positive generation and are verbally and visually more sophisticated, creating a whole new language through digital media and that Generation Y consumers are generally aware of the existence of private labels. The results also indicate that Generation Y consumers strongly agreed that they purchase groceries based on price and quality, meaning price and quality are very influential when purchasing groceries and that the packaging of, generally, all private label brands was not attractive hence a conclusion was made that packaging of private labeled products does not influence Generation Y's purchasing behaviour of private labels.
Keywords: House brands -- South Africa -- Eastern Cape; Young consumers -- South Africa -- Eastern Cape; Consumer behavior -- South Africa -- Eastern Cape